2005
DOI: 10.1371/journal.pgen.0010004
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Neurodegeneration in a Glaucoma Is Modified by Bax Gene Dosage

Abstract: In glaucoma, harmful intraocular pressure often contributes to retinal ganglion cell death. It is not clear, however, if intraocular pressure directly insults the retinal ganglion cell axon, the soma, or both. The pathways that mediate pressure-induced retinal ganglion cell death are poorly defined, and no molecules are known to be required. DBA/2J mice deficient in the proapoptotic molecule BCL2-associated X protein (BAX) were used to investigate the roles of BAX-mediated cell death pathways in glaucoma. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
419
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(441 citation statements)
references
References 69 publications
21
419
1
Order By: Relevance
“…Severely (SEV) affected nerves have extensive axon damage throughout the nerve and obvious axon loss. Axon numbers are significantly different between optic nerves of each damage level (39).…”
Section: Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…Severely (SEV) affected nerves have extensive axon damage throughout the nerve and obvious axon loss. Axon numbers are significantly different between optic nerves of each damage level (39).…”
Section: Methodsmentioning
confidence: 90%
“…The method of preparing, staining, and analyzing optic nerves for damage has been previously described and validated (5,8,20,27,34,39). In brief, cross-sections of optic nerve are stained with paraphenylenediamine (PPD), which stains all myelin sheaths but darkly stains the axoplasm of injured or dying axons.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also indicated axonopathy as an early feature in neurodegenerative diseases associated with excitotoxicity [13-16]. It is unclear whether the nerve degeneration associated with excitotoxicity is due to primary insult at the perikaryal level in the grey matter or a primary excitotoxic injury in the white matter.…”
Section: Introductionmentioning
confidence: 99%
“…1 In fact BAX activation appears to require at least one of these pro-apoptotic chaperones during development and after many apoptotic insults. 2 Retinal ganglion cells (RGCs) die by a BAX-dependent mechanism in development and after axonal injury, 3 a key insult in many neurodegenerations. During development BAX-dependent death of RGCs requires BBC3 (Harder and Libby 4 and Supplementary Figure 1A); however, the molecules controlling BAX activation after axonal injury are unknown.…”
mentioning
confidence: 99%